Improving thermoelectric performance of TiNiSn by mixing MnNiSb in the half-Heusler structure. Issue 2 (19th December 2016) - Berry, T.; Ouardi, S.; Fecher, G. H.; Balke, B.; Kreiner, G.; Auffermann, G.; Schnelle, W.; Felser, C.
Abstract : We synthesized a Ti1− x Mn x NiSn1− x Sb x system which is a promising thermoelectric material over the substitution range of x = 0.01–0.05. Abstract : The thermoelectric properties of the n-type semiconductor TiNiSn were optimized by partial substitution with metallic MnNiSb in the half Heusler structure. Herein, we study the transport properties and intrinsic phase separation in the Ti1− x Mn x NiSn1− x Sb x system. The alloys were prepared by arc-melting and annealed at temperatures obtained from differential thermal analysis and differential scanning calorimetry results. The phases were characterized using powder X-ray diffraction patterns, energy-dispersive X-ray spectroscopy, and differential scanning calorimetry. After annealing, the majority phase was TiNiSn with some Ni-rich sites, and the minority phases were primarily Ti6 Sn5, Sn and MnSn2 . The Ni-rich sites were caused by Frenkel defects; this led to metal-like behavior in the semiconductor specimens at low temperature. For x ≤ 0.05 the samples showed an activated conduction, whereas for x > 0.05 they showed metallic character. The figure of merit for x = 0.05 was increased by 61% ( zT = 0.45) in comparison with the pure TiNiSn.